"Thank you, but I think I'll sit this one out!" [The Japanese refusing to join Australia, Britain, France and Germany in Nixon's strategy to float their economies] - McCrae, Stewart, 1919-2008. (1969)
"Let Nixon's academy of dancing float you to success".
Title devised by cataloguer.
Published in the Courier Mail.
Part of the Stewart McCrae cartoon collection.
Also available online
Keywords: Nixon, Richard M. -- 1913-1994 -- Caricatures and cartoons; McMahon, William, -- 1908-1988 -- Caricatures and cartoons; Heath, Edward -- Caricatures and cartoons; Pompidou, Georges, -- 1911-1974 -- Caricatures and cartoons; Brandt, Willy, -- 1913-1992 -- Caricatures and cartoons; Monetary policy -- United States -- Caricatures and cartoons; United States -- Foreign relations -- Caricatures and cartoons